Surface Capping Agents and Their Roles in Shape‐Controlled Synthesis of Colloidal Metal Nanocrystals. Issue 36 (9th June 2020) - Yang, Tung‐Han; Shi, Yifeng; Janssen, Annemieke; Xia, Younan
Abstract: Surface capping agents have been extensively used to control the evolution of seeds into nanocrystals with diverse but well‐controlled shapes. Here we offer a comprehensive review of these agents, with a focus on the mechanistic understanding of their roles in guiding the shape evolution of metal nanocrystals. We begin with a brief introduction to the early history of capping agents in electroplating and bulk crystal growth, followed by discussion of how they affect the thermodynamics and kinetics involved in a synthesis of metal nanocrystals. We then present representative examples to highlight the various capping agents, including their binding selectivity, molecular‐level interaction with a metal surface, and impacts on the growth of metal nanocrystals. We also showcase progress in leveraging capping agents to generate nanocrystals with complex structures and/or enhance their catalytic properties. Finally, we discuss various strategies for the exchange or removal of capping agents, together with perspectives on future directions. Abstract : A pivotal role in directing the growth of colloidal metal nanocrystals into diverse but well‐controlled shapes is played by surface capping agents. This article offers a comprehensive review of capping agents as well as their use in engineering the surface structures and catalytic properties of metal nanocrystals.